Luminosity and mass functions of galactic open clusters II: NGC 4852 - Carraro, G. (2005)
We present wide-field deep UBVI photometry for the previously unstudied open cluster NGC 4852 down to a limiting magnitude I ∼ 24, obtained from observations taken with the Wide Field Imager camera on-board the MPG/ESO 2.2 m telescope at La Silla (ESO, Chile). These data are used to obtain the first estimate of the cluster basic parameters, to study the cluster spatial extension by means of star counts, and to derive the Luminosity (LF) and Mass Function (MF). The cluster radius turns out to be 5.0 ±1.0 arcmin. The cluster emerges clearly from the field down to V = 20 mag. At fainter magnitudes, it is completely confused with the general Galactic disk field. The stars inside this region define a young open cluster (200 million years old) 1.1 kpc far from the Sun (m - M = 11.60, E(B - V) = 0.45). The Present Day Mass Functions (PDMF) from the V photometry is one of the most extended in mass obtained to date, and can be represented as a power-law with a slope α = 2.3 ± 0.3 and (the Salpeter MF in this notation has a slope α = 2.35), in the mass range 3.2 ≤ m/m⊙ ≤ 0.6. Below this mass, the MF cannot be considered as representative of the cluster MF, as the cluster merges with the field and therefore the MF is the result of the combined effect of strong irregularities in the stellar background and interaction of the cluster with the dense Galactic field. The cluster total mass at the limiting magnitude results to be 2570 ±210 M⊙.